Industrial Class Partnership Management to Enhance Vocational Students’ Competence and Employability - Wajiyo, Wajiyo; Abdullah, Ghufron; Nugroho, Aryo Andri (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to examine the implementation of industrial class partnership management in enhancing students’ competence and employability at Muhammadiyah 3 Weleri Vocational School, Kendal Regency, Indonesia. The research focuses on the Motorcycle Engineering and Business program, which collaborates with PT Astra Honda Motor (AHM) through an industrial class scheme. A qualitative phenomenological approach was employed to explore managerial practices based on planning, organizing, implementation, and evaluation functions. Data were collected through in-depth interviews with the principal, vice principal for curriculum, head of expertise competency, and productive teachers, supported by documentation analysis and triangulation techniques to ensure data validity. The findings reveal that the partnership is systematically planned through curriculum synchronization, teacher upskilling, structured industrial internships, and competency-based assessment aligned with industry standards. Organizational management is carried out collaboratively between school leadership and the technical department, with clear role distribution and direct coordination with industry representatives. Implementation of the partnership includes teaching factory activities, industry-standard facilities, continuous professional development for teachers, and active student participation in national skill competitions. Evaluation is conducted regularly through industry supervision, competency testing, and performance reporting systems. The results indicate that effective industrial class partnership management significantly improves students’ technical competence, work readiness, and employment absorption, while also strengthening the school’s institutional reputation. This study highlights the importance of sustainable school–industry collaboration as a strategic model for improving vocational education quality.